(untitled) (Homoeopathy for All, 2022)
Now and then, we come across the complaint of indigestion in our routine. As the name suggests, indigestion means impaired digestion. For some, this word implies symptoms like heartburn or regurgitation, which form a part of gastroesophageal reflux disease (GERD). In addition, it may relate to belching, foetor oris or foul breath, localized pain, and discomfort in the epigastrium, among many others. According to the medical literature, indigestion is also called dyspepsia. It is a functional disorder of the gastrointestinal system. This article is an outlook on the condition and its management through an uncommon aspect of mother tinctures and low potencies, which have been mentioned often in the homeopathic literature but are infrequent in practice.